Rickshaw Pullers and Their Strategies to Deal with Everyday Conflicts in Dhaka City, Bangladesh: Rickshaw Pullers and Their Strategies (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
The rickshaw puller community commutes passengers from one place to another, making people’s busy lives easy in Dhaka city. While most studies focus on the socio-economic conditions, health hazards and survival techniques of rickshaw pullers, fewer scholarships explore different complexes and conflicts they face daily. Therefore, this paper, developed with primary data collected through semi-structured interviews and focus group discussions with some permanent and seasonal rickshaw pullers, analyses various conflicts this community faces and strategies they apply to deal with those conflicts. Drawing on Thomas-Kilmann’s Conflict Management Model that operationalises five strategies for parties in a conflict situation, it argues that rickshaw pullers mostly choose pragmatic approaches that protect their ontological needs and interests in dealing with everyday conflicts. They face conflicts in four broad aspects (e.g., economic issues, shared space, entry restriction and legal space, and personal space) and engage in conflicts with different actors, including passengers, garage owners, fellow rickshaw pullers, other vehicle drivers, traffic personnel etc., mostly over financial and individual respect issues. Although they consider power dynamics to determine the extent of engagement with the other party, they apply a competitive approach that is mostly used to deal with financial issues. Depending on the power parity of the parties, they show less self-restraint and become assertive in responding to conflicts that originate from disrespect and dishonour to them. However, they preferentially avoid conflicts when the disputing other party is more powerful than them, and avoidance is considered less costly than engaging in disputes. Due to their structural weaknesses and ignorance, rickshaw pullers often accommodate others’ demands and collaborate for common benefits. Although they reach an informal compromise through generous negotiation with passengers, garage owners and traffic personnel to balance their interests and needs, a group of other actors approach as third-party peacemakers to settle their violent engagements with other rickshaw pullers on the streets.  JASBH, Vol. 69(2), 2024, pp. 145-174